2013
DOI: 10.1016/j.chom.2013.10.014
|View full text |Cite
|
Sign up to set email alerts
|

The Lectin ERGIC-53 Goes Viral

Abstract: The biosynthesis of fusion-competent envelope glycoproteins (GPs) is a crucial step in productive viral infection. In this issue, Klaus et al. (2013) identify the cargo receptor endoplasmic reticulum (ER)-Golgi intermediate compartment 53 kDa protein (ERGIC-53) as a binding partner for viral GPs and a crucial cellular factor required for infectious virus production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…It has been demonstrated that the loss of ERGIC-53 or its activity leads to a defective assembly of virions that are unable to attach host cells. Interestingly, ERGIC-53 specifically interacts with class I viral fusion glycoproteins which also include the SARS-CoV-2 Spike protein ( Pasquato and Kunz, 2013 ). In the NCM460D cell line, much more than in the others, we assist to a high enrichment in Rabs proteins involved in the exocytic pathway such as RAB1A and RAB1B .…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that the loss of ERGIC-53 or its activity leads to a defective assembly of virions that are unable to attach host cells. Interestingly, ERGIC-53 specifically interacts with class I viral fusion glycoproteins which also include the SARS-CoV-2 Spike protein ( Pasquato and Kunz, 2013 ). In the NCM460D cell line, much more than in the others, we assist to a high enrichment in Rabs proteins involved in the exocytic pathway such as RAB1A and RAB1B .…”
Section: Resultsmentioning
confidence: 99%
“…Viral propagation is enabled when the targets such as stress granule (SG)‐associated Ras GTPase‐activating protein‐binding protein 1 (G3BP1) and heterogeneous nuclear ribonucleoproteins (hnRNPs) get relocated in cytoplasmic punctuated structures and further gets attached with NP 42 . GP is delivered to budding sites via the ER‐Golgi Pathway with the help of host factors such as ADP‐ribosylation factor 1, a GTP‐binding protein, which operates in the ER–Golgi complex, and ER–Golgi Intermediate Compartment 53 kDa protein (ERGIC‐53) 43 . The profile of the lipid on the plasma membrane determines the acceptance of glycoprotein into virions.…”
Section: Nature Of Infectious Agents (Structural and Molecular)mentioning
confidence: 99%
“…42 protein (ERGIC-53). 43 The profile of the lipid on the plasma membrane determines the acceptance of glycoprotein into virions. It is affected by lipid rafts and cholesterol content.…”
Section: Nature Of Infectious Agents (Structural and Molecular)mentioning
confidence: 99%